Spectrum of Magnetic Resonance Imaging Findings in Pancreatic and Other Abdominal Manifestations of Von Hippel-Lindau Disease in a Series of 23 patients: A Pictorial Review - Graziani, Rossella; Mautone, Simona; Vigo, Mario; Manfredi, Riccardo; Opocher, Giuseppe; Falconi, Massimo (JOP. Journal of the Pancreas, 2014)
Context Von Hippel Lindau disease is a rare autosomal dominantly inherited multisystem disorder characterized by development of benign and malignant tumors. The abdominal manifestation of the syndrome are protean. Magnetic resonance plays an important role in identification of abdominal abnormalities and follow-up of lesions. Objective To describe magnetic resonance imaging findings and patterns of pancreatic and other principal abdominal manifestations in a series of von Hippel-Lindau (VHL) disease patients and to review literature. Methods We retrospectively reviewed abdominal magnetic resonance studies performed in 23 patients (10 males, 13 females) diagnosed of VHL. Results In all examined patients abdominal involvement was present. The pancreatic imaging findings detected were: unilocular cystic lesions (6/23: 26.1%); serous cystadenomas (11/23: 47.8%), including diffuse lesions (8/23: 34.8%); solid neuroendocrine tumors (8/23: 34.8%); cystic neuroendocrine tumors (1/23: 4.3%). The renal findings detected were: simple renal cysts (18/23: 78.3%); complex renal cysts (13/23: 56.5%), including benign lesions (10/23: 43.5%) and malignant lesions (3/23: 13.0%); renal carcinomas (11/23: 47.8%) and 5 of these (45.5%) were multiple and bilateral. Five patients (21.7%) presented pheochromocytoma (4 of these were bilateral; 80.0%) and 1 patient (4.3%) presented cystadenoma of the epididymis. Conclusions In VHL disease patients, magnetic resonance imaging plays an essential role in the identification of pancreatic and other abdominal lesions, in their follow-up, in the screening of asymptomatic gene carriers, and in their long-term surveillance. Image: Lobulated fluid cysts with a “bunch of grapes” pattern.